2021
DOI: 10.3892/or.2021.8057
|View full text |Cite
|
Sign up to set email alerts
|

CD244+ polymorphonuclear myeloid‑derived suppressor cells reflect the status of peritoneal dissemination in a colon cancer mouse model

Abstract: Despite the recent development of chemotherapeutic agents, the prognosis of colorectal cancer (CRC) patients with peritoneal dissemination (PD) remains poor. The tumor immune microenvironment (TIME) has drawn attention as a key contributing factor of tumor progression. Of TIME components, myeloid-derived suppressor cells (MDSCs) are considered to play a responsible role in the immunosuppressive characteristics of the TIME. MDSCs are classified into two major subsets: Monocytic MDSCs (M-MDSCs) and polymorphonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Recent studies have revealed the landscape of i.p. immunity mediated by not only inflammatory macrophages [9] , but also immunosuppressive cells, such as MDSCs [31] and Tregs [32] . IL33 and GDF15 might be, at least partly, underlying the identified mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed the landscape of i.p. immunity mediated by not only inflammatory macrophages [9] , but also immunosuppressive cells, such as MDSCs [31] and Tregs [32] . IL33 and GDF15 might be, at least partly, underlying the identified mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures used in this experiment have been published previously [ 25 ]. Briefly, female C57BL/6J mice (8–12 weeks old) were purchased from CLEA Japan (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The procedures used in this experiment have been published previously [ 25 ]. Briefly, the EG7 cell line (a clone of EL4 murine thymoma cells expressing OVA) was purchased from American Type Culture Collection (Manassas, VA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations